Natural Catastrophes and Role of Pakistani Mass Media - Lubna Zaheer (Journal of Political Studies, 2016)
It is largely considered that mass media has an important role in mitigating the effects of natural catastrophes. This paper reviews the current knowledge about the role of media in the wake of natural calamities and hazards. It also discusses the role of Pakistani mass media during catastrophic situations. Although Pakistan is prone to natural calamities and has very vibrant media landscape, it has been observed that regrettably Pakistani media doesn’t play substantial role in disaster risk management. The role is particularly absent in the pre-disaster period. It is said that in Pakistan media can be very helpful in crisis management if it functions aptly. It is suggested that Pakistani media organizations, disaster management officials and policymakers should establish a liaison with each other to alleviate the devastating impact of natural calamities. Besides, there is a dire need for some code of conduct for media coverage of natural hazards.